Cost Behavior Analysis and Categorization - Ella Anastasya Sinambela; Mohammad Djaelani (metromedia.education, 2022)
To achieve company goals, company managers will implement a fairly reliable strategy. One of the strategies implemented is the cost efficiency required by the company. Every company has many types of costs or expenses. To get information about costs that match the actual situation, managers need to conduct cost behavior analysis. It is necessary to identify and classify costs. Under certain conditions, managers still have difficulty determining cost behavior. This paper was conducted to determine the classification of production costs in accordance with the analysis of cost behavior. Costs are classified into fixed costs, variable costs, or semi-fixed costs or semi-variable costs. Each cost category has a specific explanatory function. Accuracy in determining the cost group will determine the quality of financial reporting. In addition, it can provide valid considerations for management to make decisions.